Effectiveness of exercise interventions on urinary incontinence and pelvic organ prolapse in pregnant and postpartum women: Umbrella review and clinical guideline development - Ryhtä Iina; Axelin Anna; Parisod Heidi; Holopainen Arja; Hamari Lotta (Wolter Kluwers, 2025)
Introduction and aims:
Dysfunction related to pelvic floor muscles (PFM) is common among pregnant and postpartum women and can cause symptoms such as urinary incontinence or pelvic organ prolapse (POP). As part of developing a nationwide clinical practice guideline for nursing in Finland, the aim of this umbrella review is to summarize the existing evidence about the effectiveness of exercise interventions on urinary incontinence and POP in pregnant and postpartum women. To promote knowledge translation, recommendations for health care professionals are presented.
Methods:
We conducted an umbrella review to summarize the existing evidence. The JBI methodology for umbrella reviews was used to guide the review. The level of evidence was evaluated using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach, and recommendations based on the evidence were formulated by a clinical guideline working group.
Results:
Altogether, 9 systematic reviews, reporting findings from 89 original studies, were included. The methodological quality of the reviews was evaluated using JBI's checklist. The highest level of evidence was found for preventing the symptoms of postpartum urinary incontinence through exercise and pelvic floor muscle training (PFMT) during pregnancy. Moderate-level evidence showed that exercise and PFMT are likely to reduce the symptoms and severity of urinary incontinence, but the level of evidence was low on PFMT reducing the symptoms of POP.
Conclusion:
We recommend encouraging and guiding pregnant and postpartum women to exercise and train PFM. We also recommend identifying pregnant and postpartum women with symptoms of PFM dysfunction and directing them to a physiotherapist or other health care professional specializing in pelvic floor function.